Model "Market Day" Sebagai Upaya Untuk Memperluas Pendekatan Pembelajaran Yang Ramah Anak di RA Nurur Rahmah - Listiana, Heni; Zilfania Qathrun Nada; Najwa Afcarina Izzati; Ririn Widiyawati; Mohammad Holis (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Entrepreneurship education for young children has become a primary focus in efforts to provide relevant and profound learning experiences for them. This research discusses the "Market Day" learning model at RA Nurur Rahmah to integrate entrepreneurial skills into early childhood education curriculum. Using a qualitative approach and case study methodology, this research aims to understand the implementation of the learning model and its impact on the development of children's entrepreneurial skills. Data were collected through participatory observation and interviews, highlighting the importance of active participation from both teachers and students. The results indicate that this model provides practical experiences for students to understand basic business concepts such as production, marketing, and sales. They also develop skills such as creativity, innovation, independence, and teamwork. However, the evaluation highlights some challenges, including students' dependence on parental assistance, lack of decoration concepts, and insufficient preparation to handle a larger number of customers than anticipated. Therefore, this research emphasizes the need for adjustments and improvements in implementing the "Market Day" model to achieve optimal learning objectives. This study provides valuable insights for educational institutions and teachers in designing effective learning models to develop entrepreneurial skills in young children. It not only contributes to the development of inclusive and relevant early childhood education curricula but also supports the vision of schools that care about the holistic development of children as part of the concept of child-friendly schools.